Repeated treatments of Capan-1 cells with PARP1 and Chk1 inhibitors promote drug resistance, migration and invasion. Issue 1 (31st December 2022) - Guo, Ne; Li, Meng-Zhu; Wang, Li-Min; Chen, Hua-Dong; Song, Shan-Shan; Miao, Ze-Hong; He, Jin-Xue
ABSTRACT: PARP1 and Chk1 inhibitors have been shown to be synergistic in different cancer models in relatively short time treatment modes. However, the consequences of long-term/repeated treatments with the combinations in cancer models remain unclear. In this study, the synergistic cytotoxicity of their combinations in 8 tumor cell lines was confirmed in a 7-day exposure mode. Then, pancreatic Capan-1 cells were repeatedly treated with the PARP1 inhibitor olaparib, the Chk1 inhibitor rabusertib or their combination for 211–214 days, during which the changes in drug sensitivity were monitored at a 35-day interval. Unexpectedly, among the 3 treatment modes, the combination treatments resulted in the highest-grade resistance to Chk1 (~14.6 fold) and PARP1 (~420.2 fold) inhibitors, respectively. Consistently, G2/M arrest and apoptosis decreased significantly in the resulting resistant variants exposed to olaparib. All 3 resistant variants also unexpectedly obtained enhanced migratory and invasive capabilities. Moreover, the combination treatments resulted in increased migration and invasion than olaparib alone. The expression of 124 genes changed significantly in all the resistant variants. We further demonstrate that activating CXCL3-ERK1/2 signaling might contribute to the enhanced migratory capabilities rather than the acquired drug resistance. Our findings indicate that repeated treatments with the rabusertib/olaparib combination result in increased drug resistance and a more aggressive cell phenotype than those with either single agent, providing new clues for future clinical anticancer tests of PARP1 and Chk1 inhibitor combinations.